BUFFERING EFFECTS OF PERCEIVED SOCIAL SUPPORT BETWEEN SELF-COMPASSION AND WORK-FAMILY CONFLICT IN FEMALE SCHOOL TEACHERS: A CROSS-SECTIONAL STUDY (Contemporary Journal of Social Science Review, 2025)
Work-family conflict is a prevalent issue among female school teachers, often impacting their mental health and overall well-being. The role of self-compassion and perceived social support can provide valuable insights into mitigating these challenges and promoting work-life balance. The present study was conducted with the aim of investigating the moderating effects of perceived social support on the relationship between self-compassion and work-family conflict among female school teachers across rural and urban areas of Punjab, Pakistan. A cross-sectional correlational research design and purposive sampling technique was used to collect date (N=300; n=150 from rural and n=150 from urban) from the women school teachers by using three tools i.e., Self-Compassion Scale, Multidimensional Scale of Perceived Social Support, and Work-Family Conflict. The results revealed that self-compassion and perceived social support was significant negative correlated with work-family conflict. Along with this, perceived social support was found significant moderator between the relationship of self-compassion and work-family conflict in female school teachers. Moreover, the results showed that work-family conflict found more in the women teaching into the urban area rather than rural area of the Punjab. It was concluded that study highlights the critical role of perceived social support in mitigating the challenges of work-family conflict among female school teachers, particularly in urban areas. Promoting self-compassion and fostering supportive networks can help enhance their work-life balance and overall well-being.